Assessing the relationship between youth religiosity and their alcohol use: A meta-analysis from 2008 to 2018. (July 2020) - Russell, Alex M.; Yu, Bo; Thompson, Christopher G.; Sussman, Steve Y.; Barry, Adam E.
Highlights: This meta-analysis highlights the protective effects of youth religiosity on their alcohol use. Religiosity measure type was a statistically significant moderator of the protective effect. National surveys attempting to measure religiosity and its relationship with alcohol use may benefit from assessing additional dimensions of religiosity. There is a need to explore interactions between varying dimensions of religiosity and alcohol use. Abstract: Objective: Underage alcohol use, and associated deleterious consequences, persists as a serious public health issue. In particular, early initiation of alcohol use increases risk for the development of alcohol use disorders later on in life. Religiosity – a multidimensional construct, encompassing personal beliefs, commitments, practices, and public behaviors – has demonstrated a strong protective effect on alcohol consumption; as one's religiosity increases their alcohol use behaviors decrease. This meta-analysis includes research spanning years 2008–2018, and specifically examines whether measuring religiosity via a single dimension, as compared to multiple dimensions, impacts the association between alcohol use and religiosity. Method: A systematic electronic database search spanning three databases using relevant key terms was conducted. Overall, 16 studies were deemed appropriate for subsequent analyses. Effect sizes were calculated, homogeneity of effect sizes was assessed, overall weighted effects were computed, and moderator analyses were conducted to examine the effects of study-level characteristics on the variability of effect sizes. Results: Religiosity demonstrated a statistically significant protective effect on adolescent alcohol use ( Z = −0.21, p  < .001). Measurement of religiosity (i.e., unidimensional versus multidimensional) explained a statistically significant amount of effect-size heterogeneity ( Qb (1) = 7.38, p  = .007). Thus, religiosity measure dimensionality had a significant effect on the protective effect of youth religiosity on alcohol use. Conclusion: Results highlight the protective effect of youth religiosity on alcohol use. To further understand the scope of this protective association, future research would benefit from exploring the multidimensional nature of religiosity and the associations between varying conceptualizations of religiosity and adolescent alcohol use outcomes.